(untitled) (Journal of Informatics Education and Research, 2026)
In rapidly evolving business world, transforming a company vision into tangible outcomes relies apart from effective planning but also on the optimal utilization of employee skills and talents. Using data collected from 112 employees in Chennai city. The study applies a chi square, linear regression and independent sample t test to analyses relationship between vision planning employee engagement and employee optimizations. This paper presents framework to connect clear planning of organisational goals with helping employees perform at their best. Its shows how aligning individual work with company goal boosts productivity, innovation and supports to promote a success. Vision realisation is about setting clear goals from a company broad plan and making sure everyone understand their role in reaching these goals. Strong leadership and effective communication enable employees to recognize how their tasks align with the overall vision. At the same time employee optimization means managing hiring, training and motivation to ensure that workforce skills align with company requirements. Using data and feedback is key to this connection. By tracking employee performance and skills in real time, companies can quickly find where training or support is needed. Personalised growth plans further engage workers by focusing on their strengths and career goals.